Reflections on the use of labour market indicators in designing policies with a gender-based approach - Pollack, Molly (UN SantiagoCL, 1998)
Looks at the indicators that now exist and are published in the region, and that serve as a basis for designing policies and programmes aimed at improving the lot of vulnerable groups. Sets forth the limitations of these indicators as tools for measuring the labour market participation of men and women, with particular emphasis on their shortcomings as regards the activity of women. Puts forward proposals for indicators better able to measure the activity of women in the labour market and to serve as inputs for policies and programmes.